A Comparative Study of Students of Government and Non-government Schools in Reading and Writing of Mother Tongue - Dvivedi, Sweta (JOURNAL OF INDIAN EDUCATION, 2015)
The quality of education and its determinants remain a topic of attention since the beginning of formal education. Though there are a number of factors which determine the quality of education, the most vital one that attracts the attention of all is the level of achievement. For any nation of the world these levels of achievement are so important that they need to be known periodically to keep a tab on the general health of the education system. But there is a big gap in the level of achievement in different types of schools. Factors, such as semi qualified teachers, very high student-teacher ratio, inappropriate teachinglearning materials and out-dated teaching methods result in a low quality of education. As a result, there are many students who even after completing primary schooling lack even in rudimentary reading and writing skills. Governing body of the schools is also other prominent factor for this. In India a large population of children study in the government schools and researches indicate that the outcome of the government schools is not up to the mark. The following paper investigates this perception in the context of reading and writing skills of children in their mother tongue.